2018
DOI: 10.3389/fmicb.2018.01990
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Subspecies Variation and Nematode Grazing Change P Dynamics in the Wheat Rhizosphere

Abstract: Low phosphorus soils are thought to constitute the majority of soils worldwide and cannot support intensive agriculture without high fertilizer inputs. Rhizobacteria are well-known to modify P dynamics and an increased bacterial diversity normally has a positive impact on various process rates. However, it is not known how variation in bacterial diversity at the subspecies level could influence trophic interactions in the rhizosphere and its consequences on plant P nutrition. We therefore hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…In addition, grazing might release P assimilated in bacterial biomass and making it more available to plant roots. (Irshad et al, 2011;Irshad et al, 2012Irshad et al, : 2018 claimed that the bacteria with their grazer nematodes have increased the availability of P from organic and inorganic sources in controlled conditions and our results could serve the extension of their findings in soil conditions. Richardson and Simpson, (2011) reported that the grazing activity upon PSB populations could be as efficient as the production of free P from insoluble mineral P. The treatments without TCP showed no difference or even negative effect of inoculation in case of root P which might be due to increased competition among plant roots, bacteria and nematodes without any added P resource.…”
Section: Phosphorus In Roots and Shoots With Or Without Tcpsupporting
confidence: 73%
See 2 more Smart Citations
“…In addition, grazing might release P assimilated in bacterial biomass and making it more available to plant roots. (Irshad et al, 2011;Irshad et al, 2012Irshad et al, : 2018 claimed that the bacteria with their grazer nematodes have increased the availability of P from organic and inorganic sources in controlled conditions and our results could serve the extension of their findings in soil conditions. Richardson and Simpson, (2011) reported that the grazing activity upon PSB populations could be as efficient as the production of free P from insoluble mineral P. The treatments without TCP showed no difference or even negative effect of inoculation in case of root P which might be due to increased competition among plant roots, bacteria and nematodes without any added P resource.…”
Section: Phosphorus In Roots and Shoots With Or Without Tcpsupporting
confidence: 73%
“…Acid phosphatase activity (phosphomonoesterase) was analyzed by the method as modified by (Irshad and Yergeau, 2018). Briefly, the rhizoplane soil samples were incubated with p-nitrophenyl phosphate (p-NPP) as a substrate for enzyme activity for 1 hour.…”
Section: Measurement Of Phosphatase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipids and phytate are major organic P pool in soils, which can be hydrolyzed by phosphatase and phytase, respectively (Maougal et al, 2014;Neal et al, 2017;Irshad and Yergeau, 2018). Previous literatures have reported that alkaline phosphatase is exclusively originated from soil microorganisms, and acid phosphatase is mainly produced and secreted by plants (Krämer and Green, 2000;Fraser et al, 2015).Three prokaryotic genes, phoX, phoA, and phoD, are responsible for encoding alkaline phosphatase (Huang et al, 2009); three genes of bpp encoding β-propeller phytase, ptp encoding protein tyrosine phosphatase, and hap encoding histidine acid phosphatase are found in prokaryote (Lim et al, 2007;Neal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among various abiotic stresses, salinity stress and phosphorus deficiency are two worldwide problems and restrict intensive agriculture [1,2]. As one of the major abiotic stresses, salinity affects crop production in arid and semiarid areas, which grow wheat as the major crop.…”
Section: Introductionmentioning
confidence: 99%